136k views
7 votes
Solve 5p(2p - 3)(p + 7) = 0.
p=___, p=____, p=_____

Solve 5p(2p - 3)(p + 7) = 0. p=___, p=____, p=_____-example-1
User Orch
by
5.6k points

2 Answers

13 votes

Answer:

p=0, p=1.5, p=-7

Explanation:

Assuming we need the equation to equal zero we do this.

5p(2p-3)(p+7)

5p = 0 (2p-3) = 0 (p+7)= 0 Separate each part

5(0) = 0 2(1.5)-3 = 0. (-7)+7 = 0 Replace P so the outcome is 0

p=0, p=1.5, p=-7 Solution

User SpicyClubSauce
by
6.2k points
11 votes

Answer:

5p(2p-3)(p+7)=0

10p-15 p +7 =0

10p+p=0+15-7

11p =8

11p=8

p=8/11

User Tim McNamara
by
5.7k points